Executing Practices - Pritchard, Helen; Snodgrass, Eric; Tyżlik-Carver, Magda (DATA browser book series, 2018)
This collection brings together artists, curators, programmers, theorists and heavy internet browsers, all of whose practices make a critical intervention into the broad concept of execution. It draws attention to their political strategies, asking: who and what is involved with those practices, and for whom or what are these practices performed, and how? From the contestable politics of emoji modifier mechanisms and micro-temporalities of computational processes to genomic exploitation and the curating of digital content, the chapters account for gendered, racialized, spatial, violent, erotic, artistic and other embedded forms of execution. Together they highlight a range of ways in which execution emerges and how it participates within networked forms of liveliness. With contributions by Roel Roscam Abbing, Geoff Cox, Olle Essvik, Jennifer Gabrys, Francisco Gallardo, David Gauthier, Brian House, Yuk Hui, Peggy Pierrot, Andy Prior, Helen Pritchard, Linda Hilfling Ritasdatter, Audrey Samson, Susan Schuppli, Kasper Hedegård Shiølin, Eric Snodgrass, Winnie Soon, Femke Snelting, Marie Louise Juul Søndergaard, and Magda Tyżlik-Carver.